PERSPEKTIF QŌHELET MENCAPAI “FINISHING WELL” DALAM STRUKTURPERALELISME KOMPARATIF BERDASARKAN PENGKHOTBAH 7:8 7:8 - Pattinaja, Aska Aprilano (Jurnal Teologi RAI, 2024)
This study examines the concept of "finishing well," which appears in the structure of comparative parallelism, as an emphasized Qōhelet perspective. This verse temporarily contrasts the beginning and the end, indicating that the end is better when done with patience and wisdom. In the literature search, it was found that the study of this text is rarely done, as it is often included in the discussion of the advice of wisdom in this passage. Based on the method of hermeneutic study of the sub-genre of wisdom literature, this study found that there are three perspectives of Qōhelet that encourage one to achieve "finishing well," namely: first, patience as the main factor; second, focusing on the goal; third, avoiding pride. These are the main factors that should be applied to achieve a glorious ending. Every child of God should make these factors the basis of character building in order to persevere to the end.